2010
DOI: 10.1038/emboj.2010.63
|View full text |Cite
|
Sign up to set email alerts
|

The SNAG domain of Snail1 functions as a molecular hook for recruiting lysine-specific demethylase 1

Abstract: Epithelial-mesenchymal transition (EMT) is a transdifferentiation programme. The mechanism underlying the epigenetic regulation of EMT remains unclear. In this study, we identified that Snail1 interacted with histone lysine-specific demethylase 1 (LSD1). We demonstrated that the SNAG domain of Snail1 and the amine oxidase domain of LSD1 were required for their mutual interaction. Interestingly, the sequence of the SNAG domain is similar to that of the histone H3 tail, and the interaction of Snail1 with LSD1 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
380
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(397 citation statements)
references
References 65 publications
15
380
2
Order By: Relevance
“…Previous reports linked Lsd1 with NuRD and CoREST complex to regulate EMT-related processes in cancer progression and in cell culture-based EMT assays 17,[36][37][38] . More specifically, Wang et al 17 showed that LSD1 influences the metastatic potential of breast cancer cell line MDA-MB-231.…”
Section: Discussionmentioning
confidence: 98%
“…Previous reports linked Lsd1 with NuRD and CoREST complex to regulate EMT-related processes in cancer progression and in cell culture-based EMT assays 17,[36][37][38] . More specifically, Wang et al 17 showed that LSD1 influences the metastatic potential of breast cancer cell line MDA-MB-231.…”
Section: Discussionmentioning
confidence: 98%
“…Interactions of several LSD1-CoREST subunits with some transcription factors (11,(24)(25)(26) or with long noncoding RNAs (27) The SANT2 domain of CoREST is required for the efficient demethylation of nucleosomes by the LSD1-CoREST dimer and seems to be essential for a correct presentation of the substrate to the LSD1 catalytic site (29). The role of the HMG domain of Braf35 is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…17 Likewise, a transcriptional repressor Snail1, which is a known interacting partner of HDACs, was shown to recruit LSD1 to its target gene promoter and lead to the suppression of E-cadherin expression increasing cell migration. 18 Moreover, LSD1 is functionally linked to DNA methylation and subsequent gene silencing. DNMT3L, a noncatalytic paralog of de novo DNMT3A and -3B, specifically interacts with the histone H3 tail, only when H3K4 is unmethylated.…”
Section: Lsd1/kdm1amentioning
confidence: 99%